An awareness of private car drivers in Masai Johor towards the usage of natural gas vehicle as an alternative fuel - Ramzi Mohd Nor, Mohd; Zani Muhamad, Muhamad; Abdullah, Rozelin; Suriani Mat Daud, Mimi; Ahmad, Faradina (International Journal of Engineering and Technology, 2018)
This research has studied the level of awareness among the private car drivers in Masai Johor towards the usage of natural gas vehicle (NGV) as an alternative fuel to gasoline and diesel. The awareness of  the private car drivers as the biggest community of the road users, would help in reducing air pollution, greenhouse effect and at the same time contributes to green environment. On the other hand, the lack of awareness on the usage of NGV as an alternative fuel would remain the dependency on gasoline or diesel which in long run would produce harmful pollutants to environment and diminish the fossil fuel supply in future. This research is intended to find out the level of awareness on the usage of NGV and also to find out the factors that contribute to the lack of NGV users in Masai Johor. Research is carried out using both qualitative and quantitative method where questionnaires, interviews and observation have been done in collecting the data. From the study, the researcher has found out that most of the private car drivers in Masai Johor are aware of the NGV as an alternative fuel but only small numbers of them have been using the NGV due to some constraints and having bad perceptions on the NGV.  NGV is not just a cost saving, but also could reduce air pollution and proven to be among the best alternative fuel which indirectly reduces the dependency on gasoline and diesel thus create better and healthy environment.